Risk for SARS-CoV-2 Infection in Healthcare Workers, Turin, Italy - Calcagno, Andrea; Ghisetti, Valeria; Emanuele, Teresa; Trunfio, Mattia; Faraoni, Silvia; Boglione, Lucio; Burdino, Elisa; Audagnotto, Sabrina; Lipani, Filippo; Nigra, Marco; D’Avolio, Antonio; Bonora, Stefano; et al. (Emerging infectious diseases, 2021)
We measured severe acute respiratory syndrome coronavirus 2 spike protein subunits S1/S2 antibodies by using capillary electrophoresis and a chemiluminescence immunoassay for 5,444 active healthcare workers in Italy. Seroprevalence was 6.9% and higher among participants having contact with patients. Seroconversion was not observed in 37/213 previously infected participants.